The Effects of Watching Authentic English Videos with and Without Subtitle on EFL Learner’s Motivation in Listening Skills at SMAN 3 Kediri - Annisa Agung Rahmadhani; Rika Riwayatiningsih; Dewi Kencanawati (Westscience Press, 2024)
This study aims to examine the effect of watching original English videos with or without subtitles on the listening ability of EFL students at SMA 3 Kediri. This research uses quantitative methods. The research participants consisted of a group of EFL students, taken from class XII-IPS 2 at SMAN 3 Kediri. And data is collected through tests from previous listening results and questionnaires. This intervention involved exposing participants to original English-language videos in two conditions: one with English subtitles and the other without English subtitles. Motivational factors influencing student engagement with learning materials were explored through analysis of questionnaire responses. The findings show that the use of subtitles has a significant effect on students' listening abilities, while most students are motivated to watch English films. The recommendations of this research can help develop learning approaches that suit the needs of EFL students in the region.